Freefall : America, free markets, and the sinking of the world economy - Stiglitz, Joseph E. (New York : W. W. Norton & Co., 2010)
Nobel Laureate Joseph E. Stiglitz explains how America exported bad economics, bad policies and bad behavior to the rest of the world. When World markets began to fail, America put together a haphazard response. Stiglitz outlines his responses to address the inequalities in the global financial and challenges economists for good ideas.
The making of a crisis -- Freefall and its aftermath -- A flawed response -- The mortgage scam -- The great American Robbery 0-- Avarice triumphs over prudence -- A new capitalist order -- From global recovery to global prosperity -- Reforming economics -- Toward a new society -- Afterword to the paperback edition.
Includes bibliographical references (pages [345] - 416) and index.
Donated By Akbar Ali Khan
Keywords: Financial crises -- United States; Finance -- Government policy -- United States; Global Financial Crisis, 2008-2009.; Economics; United States -- Economic policy -- 1993-2001.; United States -- Economic policy -- 2001-2009.